Bukhara-Iran relations in XVII–XVIII centuries - Nekzad K. M. (Interactive science, 2017)
the article describes Bukhara-Iran relations in XVII–XVIII centuries, which were hostile and difficult due to the bloody battles of these countries for their territorial expansion. Safavids primarily wanted to seize Balkh, as it was an important strategic base for the invasion in Maverannahr hinterland. Balkh leaders took an active part in the fight against Safavids.
Keywords: отряд; Iran; Иран; Сефевиды; правитель; Балх; взаимоотношение; Бухара; Хорасан; войско; набеги; посол; осада; Balkh; relationship; Safavids; Bukhara; Khorasan; detachment; army raids; the governor; ambassador; siege